Herpes Simplex Type 1 UL43 Multiple Membrane-Spanning Protein Increases Energy Metabolism in Host Cells through Interacting with ARL2 - Jianshan Deng; Zhiying Zhong; Chengxu Geng; Zhenning Dai; Weihan Zheng; Ziyue Li; Zi Yan; Jiaxin Yang; Wenfeng Deng; Wei Tan; Hanxiao Sun; Shiyu Li (Cells, 2022)
Non-essential proteins for viral replication affect host cell metabolism, while the function of the UL43 protein of herpes simplex virus 1 (HSV-1) is not clear. Herein, we performed a comprehensive microarray analysis of HUVEC cells infected with HSV-1 and its UL43-deficient mutant and found significant variation in genes associated with cellular energy metabolic pathways. The localization of UL43 protein in host cells and how it affects cellular energy metabolism pathways were further investigated. Internalization analysis showed that the UL43 protein could be endocytosis-mediated by YPLF motif (aa144–147) and localized to mitochondria. At the same time, more ATP was produced by coupling with mitochondrial small G protein ARF-like 2 (ARL2) GTPase, which triggered the phosphorylation of ANT1 (SLC25A4) to affect the opening degree of mitochondrial permeability transition pore (mPTP), and significantly promoted the aerobic oxidation and oxidative phosphorylation of glucose. Our study shows that UL43 mediates the improvement of host cell metabolism after HSV-1 infection. Additionally, UL43 protein could be a valuable ATP-stimulating factor for mammalian cells.